Trends in neonatal mortality and morbidity in very-low-birth-weight (VLBW) infants over a decade: Singapore national cohort study - Jiun Lee; Cheryl Yen May Lee; Krishnamoorthy Naiduvaje; Yoko Wong; Ashwani Bhatia; Imelda Lustestica Ereno; Selina Kah Yin Ho; Cheo Lian Yeo; Victor Samuel Rajadurai (Pediatrics and Neonatology)
Background: Very preterm infants are at risk for neurodevelopmental impairment because of postnatal morbidities. This study aims to (1) compare the outcomes of very-low-birth-weight (VLBW) infants in Singapore during two time periods over a decade; 2) compare performances among Singaporean neonatal intensive care units (NICUs); and 3) compare a Singapore national cohort with one from the Australian and New Zealand Neonatal Network (ANZNN). Methods: Singapore national data on VLBW infants born during two periods, 2007–2008 (SG2007, n = 286) and 2015–2017 (SG2017, n = 905) were extracted from patient medical records. The care practices and clinical outcomes among three Singapore NICUs were compared using SG2017 data. Third, using data from the ANZNN2017 annual report, infants with gestational age (GA) ≤29 weeks in SG2017 were compared with their Oceania counterparts. Results: SG2017 had 9.9% higher usage of antenatal steroids (p < 0.001), 8% better survival for infants ≤26 weeks (p = 0.174), and used 12.7% lesser nonsteroidal anti-inflammatory drugs for patent ductus arteriosus closure (p < 0.001) than those of SG2007 cohort. Rate of late-onset sepsis (LOS) was almost halved (7.4% vs. 14.0%, p < 0.001), and exclusive human milk feeding after discharge increased threefold (p < 0.001). SG2017, in contrast, had a higher rate of chronic lung disease (CLD) (20.0% vs. 15.1%, p = 0.098). Within SG2017, the rates of LOS, CLD, and human milk feeding varied significantly between the three NICUs. When compared with ANZNN2017, SG2017 had significantly lower rates of LOS for infants ≤25 weeks (p = 0.001), less necrotizing enterocolitis for infants ≤27 weeks (p = 0.002), and less CLD across all GA groups. Conclusion: Postnatal morbidities and survival rates for VLBW infants in Singapore have improved over a decade. Outcomes for VLBW infants varied among three Singapore NICUs, which provide a rationale for collaboration to improve clinical quality. The outcomes of Singaporean VLBW infants were comparable to those of their ANZNN counterparts.